Immune-modulating therapy with granulocyte-macrophage colony-stimulating factor (GM-CSF) in refractory rhino-orbital-cerebral mucormycosis – a case report - Thayanantham, Piremiya; Kalin-Hajdu, Evan; Dufresne, Simon; Dufresne, Philippe J.; Viau-Lapointe, Julien; Tremblay, Jan-Alexis (Frontiers in Immunology, 2025)
This report outlines the case of a woman with rhino-orbital-cerebral mucormycosis following diabetic ketoacidosis, refractory to systemic and local antifungal treatment as well as repeated extensive sinonasal debridement. Adjunctive Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) therapy was associated with significant clinical improvement. This treatment restored visual acuity, and the excellent outcomes were maintained at the 24-month follow-up. This is the first report of successful use of a short course (5 days) of GM-CSF for refractory rhino-orbital cerebral mucormycosis in an adult patient after diabetic ketoacidosis, highlighting the therapeutic potential of this pragmatic approach.